2019
DOI: 10.1021/acs.analchem.8b05521
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Identification of Ischemic Injury in Renal Tissue by Mass-Spectrometry Imaging

Abstract: The increasing analytical speed of mass-spectrometry imaging (MSI) has led to growing interest in the medical field. Acute kidney injury is a severe disease with high morbidity and mortality. No reliable cut-offs are known to estimate the severity of acute kidney injury. Thus, there is a need for new tools to rapidly and accurately assess acute ischemia, which is of clinical importance in intensive care and in kidney transplantation. We investigated the value of MSI to assess acute ischemic kidney tissue in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 52 publications
(110 reference statements)
2
20
0
Order By: Relevance
“…MALDI-TOF MS can quickly monitor the m/z of moleculars and provide mass information. It does not require chemical reagents to react with speci c molecules in samples, thereby avoiding false positive or false negative results (van Smaalen et al 2019;Grand et al 2014). In this study, MALDI-TOF MS was combined with a high-mass detector which would not induce saturate effects in the presence of complex mixture over a broad mass range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MALDI-TOF MS can quickly monitor the m/z of moleculars and provide mass information. It does not require chemical reagents to react with speci c molecules in samples, thereby avoiding false positive or false negative results (van Smaalen et al 2019;Grand et al 2014). In this study, MALDI-TOF MS was combined with a high-mass detector which would not induce saturate effects in the presence of complex mixture over a broad mass range.…”
Section: Discussionmentioning
confidence: 99%
“…Matrix-assisted laser desorption/ionization time-of-ight mass spectrometry (MALDI-TOF MS) has advantages of lower-cost and automation, and has made considerable advances in the research of cancer, cardiovascular diseases, and infectious diseases (Wang et al 2011;Wieczorek et al 2020;van Smaalen et al 2019). The direct analysis of body uids or tissue samples using MALDI-TOF MS can identify speci c biomarkers and further reveal the characteristic pathological changes of diseases (Grand et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…An interesting incidental finding in positive mode was the ring‐like distribution of lipids in Figure surrounding the most severe injury. This was interesting in another respect since the putative LPC at m/z 496.324 [M + H] + was recently posited to be a biomarker of ischemia in renal tissues . If this finding is generalized in different tissues, it would suggest a pattern of ischemia in the perimeter of the areas with the most extreme damage.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated the potential of using MSI to discriminate different degrees of renal ischemic injury in the clinic. 47 Notably, several research groups endeavored to push forward the technique of MALDI-MSI during the past decade, whereas its application is still largely limited to its resolution. 48 In most studies, MALDI-MSI is not capable of imaging molecules with resolution at the subcellular and organelle level, yet this level of resolution has been proven valuable in clinical diagnosis.…”
Section: Mass Spectrometry-based Chemical Mapping and Profiling Approachesmentioning
confidence: 99%